1998
DOI: 10.1128/jb.180.6.1402-1410.1998
|View full text |Cite
|
Sign up to set email alerts
|

Balance between Endogenous Superoxide Stress and Antioxidant Defenses

Abstract: Cells devoid of cytosolic superoxide dismutase (SOD) suffer enzyme inactivation, growth deficiencies, and DNA damage. It has been proposed that the scant superoxide (O2 −) generated by aerobic metabolism harms even cells that contain abundant SOD. However, this idea has been difficult to test. To determine the amount of O2 − that is needed to cause these defects, we modulated the O2 − concentration insideEscherichia coli by controlling the expression of SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 65 publications
(60 reference statements)
2
67
0
Order By: Relevance
“…Oxidative and nitrosative stress are common phenomena, caused by exposure of cells to ROS and RNS, both of which can damage biomolecules such as proteins, nucleic acids and cellular membranes. Under normal growth conditions, a balance exists between the amount of radicals produced and the cellular defense mechanisms [153]. Defense mechanisms against oxidative and nitrosative stress are generally under the control of SoxRS and OxyR, which exist in a variety of bacteria (for review, see [154]).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative and nitrosative stress are common phenomena, caused by exposure of cells to ROS and RNS, both of which can damage biomolecules such as proteins, nucleic acids and cellular membranes. Under normal growth conditions, a balance exists between the amount of radicals produced and the cellular defense mechanisms [153]. Defense mechanisms against oxidative and nitrosative stress are generally under the control of SoxRS and OxyR, which exist in a variety of bacteria (for review, see [154]).…”
Section: Discussionmentioning
confidence: 99%
“…It was verified that the structures of sod genes in the E8 cells were not altered under the examined conditions by the agarose gel electrophoresis after amplifying their regions by PCR (data not shown). It is documented that the SOD deficiency imposes upon E. coli auxotrophies, especially for some amino acids, under an aerobic condition [6]. In preliminary trials using the original IM303 strain, notable growth suppression occurred when threonine was and their gene structures in SODdeficient mutant IM303 and wild-type strain MM294 of E. coli.…”
Section: Properties Of Individual Cells Prevailing In Culture Of Sod-mentioning
confidence: 99%
“…It has been reported that SOD-deficient mutants of Escherichia coli exhibited several defects, such as auxotrophy for amino acids, and high frequencies of spontaneous mutagenesis when grown aerobically [6,7]. These suggest that a sublethal or moderate level of oxidative stress may exert a triggering effect on activation of specific signaling pathways, resulting in induction of altered metabolisms and cellular properties in SODdeficient E. coli cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobically growing cells are normally protected from the adverse effect of these ROSs through the activity of non-speci®c antioxidants such as reduced glutathione (GSH) and protective enzymes such as superoxide dismutase and catalase, which function to degrade these harmful agents (Storz et al 1989;Demple 1991;Storz and Imlay 1999). If, however, the intracellular concentration of ROS exceeds the level at which the cytoplasmic antioxidants and protective enzymes can detoxify these adequately, then a situation of oxidative stress will occur (Gort and Imlay 1998). During oxidative stress, important cellular enzymes and structures are damaged which lead to loss of viability within the bacterial population as a whole (Imlay et al 1988;Martinez and Kolter 1997;Tamarit et al 1998).…”
Section: Introductionmentioning
confidence: 99%